International Law Analysis on the Territorial Conflict Between Israel and Palestine - Elvira Octaviany (Fakultas Hukum, Universitas Internasional Batam, 2017)
The purpose of this research is to ascertain the reason behind the invasion of Israel to Palestine. The Invasion has started since the 19th century and caused a territorial conflict that has resulted in casualties. This research will also provide a historical analysis from the start of the Jewish invasion to Palestine and until the state of Israel and Palestine were born. This research also has the purpose to analyze what are the different approaches that has been sought by the International Law, and is it effective to resolve the conflict. The researcher will also provide the best solution to solve the conflict. This research is a normative research. Secondary data was used as the data source. The gathering of data was done by library research. After all the data were collected, the data will be processed and analyzed by qualitative way. Then a conclusion will be made from the research and will be written in descriptive. Based on this research, it can be ascertained that the reason behind the invasion of Israel to Palestine is because it is an act on where at that time the Jewish in Britain were discriminated and they need a place where they can safely settled. That action was suitable with the theory of territorial claims. It can also be analyzed that resolutions have been made by the UN, which are the UN Resolution 181 and UN Resolution 242. Negotiation had also been done resulting in Oslo Accord 1. But the approaches are considered ineffective. Israel heeds the criticism from other countries regarding the acts that were considered violating the 1949 Geneva Convention Relative to the Protection of Civilian Persons in Time of War. The best way to resolve this conflict is that the whole international community has to work together by eliminating the veto system in the UN.